Using Computer-Mediated Communication to Enhance Teacher Collaboration - Bunkley, Crystal (My University, 2006)
The purpose of this action research study was to examine the effects of computer-mediated communication to enhance teacher collaboration. The study took place within six elementary schools and involved eleven teachers who taught at grade levels ranging K-5. The teachers collaborated for twenty-three days and participated in a variety of discussion topics using the online collaboration site, Campfirenow.com. Pre and post attitudinal survey findings indicated that the teachers involved in the study enjoyed collaborating and liked having a set place to exchange ideas. The study group also felt they benefited from learning what others do in different buildings since many of them were at various locations throughout the county.
Keywords: teacher collaboration; Campfirenow.com; computer-mediated communication